CONSTRUCTION OF CORRELATION MODELS OF OSCILLATORY PROCESSES BY AN ALTERNATIVE METHOD - Sh. B. Ochilov; O. Q. Akramova; N. N. Rasulova (Journals Park Publishing, 2025)
This article examines economic processes with correlational dependencies that change over time according to a harmonic law, and it also proposes a method for determining the period, phase, and frequency of the oscillations in these processes. The article proposes a method for determining the coefficients A and B in the harmonic function, which was obtained as a result of research.
Keywords: Differential equation, finite differences, period of oscillation, frequency of oscillation, harmonic functions, cyclicity of fluctuations in crop yields, oscillation phase.